Influential Power of ’Word of Mouth’ for Purchase of Sarees - Malmarugan, D. (Indian Journal of Marketing, 2008)
One of the most widely accepted notions in consumer behavior is that Word Of Mouth(WOM), plays an important role in shaping consumers’ attitudes and behaviors. Word of Mouth is the most important source of influence in the purchase of household goods and food products. It is twice effective as radio advertising, four times as effective as personal selling, and seven times as effective as newspapers and magazines.